Book Reviews Compilation: Open Access Books on Open Scholarly Communications - Andrew Rens; Cheryl Hodgkinson-Williams; Kevin Williams; Eve Gray (The African Journal of Information and Communication, 2010)
Book Reviews Compilation: Open Access Books on Open Scholarly Communications